Magical UniCoRns - Philip, Claire; Carpenter, Sarah; Rose, Jessica; Higgins, Megan; Aguilar, Sandra; Wray, Jordan (Essex, United Kingdom : Miles Kelly Publishing Ltd., 2020)
This fantastic collection includes four original fiction stories featuring some very special unicorns. The large format allows the stunning full-bled artwork scenes to jump off the page, helping to engage and inspire younger children as they delve into a world of unicorns.
The Unicorn and the Lost Cat -- The Unicorn and the Brave Princess -- The Unicorn and the Wild Horses -- The Unicorn and the Magical Adventure.
4 short stories to share
Keywords: Unicorns -- Juvenile fiction; Cats -- Juvenile fiction; Rescue work -- Juvenile fiction; Picture books